Tunable photo-responsive elastic metamaterials - Antonio S. Gliozzi (Nature Portfolio, 2020)
Here, the authors present a light-responsive elastic metamaterial whose transmission spectrum can be tuned by light stimuli. More specifically, we demonstrate that an appropriate laser illumination is effective in reversibly widening an existing frequency band gap, doubling its initial value.